2014
DOI: 10.1016/j.ejphar.2014.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin modulates acetylcholine release at the myoneural junction

Abstract: Transient receptor potential (TRP) proteins are non-selective cation channel proteins that are expressed throughout the body. Previous studies demonstrated the expression of TRP Vanilloid 1 (TRPV1), capsaicin (CAP) receptor, in sensory neurons. Recently, we reported TRPV1 expression in mouse motor nerve terminals [MNTs; (Thyagarajan et al., 2009)], where we observed that CAP protected MNTs from botulinum neurotoxin A (BoNT/A). Phrenic nerve diaphragm nerve muscle preparations (NMP) isolated from isoflurane ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…This mechanism probably involves hydrolysis of phosphatidyl inositol (4,5) bisphosphate (PIP2) to form inositol trisphosphate and diacylglycerol via the GABA B receptor-mediated activation of PLC. There are some studies supporting this hypothesis: (i) activation of the transient receptor potential vanilloid 1 (TRPV1) channels is capable of causing a PLC-dependent PIP2 hydrolysis (Lukacs et al 2007); (ii) TRPV1 channels have been revealed in rat neuromuscular junction and their activation by capsaicin results in a selective decrease in the quantal content of stimulus evoked neurotransmitter release (as in our case) and does not influence the processes of spontaneous quantal release of ACh (Thyagarajan et al 2014). Authors of the latter paper concluded that the decrease in the membrane PIP2 level, as a function of TRPV1-PLCdependent mechanisms, is the major reason for selective depression of evoked exocytosis of ACh.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…This mechanism probably involves hydrolysis of phosphatidyl inositol (4,5) bisphosphate (PIP2) to form inositol trisphosphate and diacylglycerol via the GABA B receptor-mediated activation of PLC. There are some studies supporting this hypothesis: (i) activation of the transient receptor potential vanilloid 1 (TRPV1) channels is capable of causing a PLC-dependent PIP2 hydrolysis (Lukacs et al 2007); (ii) TRPV1 channels have been revealed in rat neuromuscular junction and their activation by capsaicin results in a selective decrease in the quantal content of stimulus evoked neurotransmitter release (as in our case) and does not influence the processes of spontaneous quantal release of ACh (Thyagarajan et al 2014). Authors of the latter paper concluded that the decrease in the membrane PIP2 level, as a function of TRPV1-PLCdependent mechanisms, is the major reason for selective depression of evoked exocytosis of ACh.…”
Section: Discussionsupporting
confidence: 59%
“…); (ii) TRPV1 channels have been revealed in rat neuromuscular junction and their activation by capsaicin results in a selective decrease in the quantal content of stimulus evoked neurotransmitter release (as in our case) and does not influence the processes of spontaneous quantal release of ACh (Thyagarajan et al . ). Authors of the latter paper concluded that the decrease in the membrane PIP2 level, as a function of TRPV1‐PLC‐dependent mechanisms, is the major reason for selective depression of evoked exocytosis of ACh.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Primarily, the expression of TRPV1 is recognized in sensory neurons. Published literature suggests that TRPV1 is also expressed in various other tissues such as the neuromuscular junction [2][3][4], adipose tissue [5][6][7], liver [8,9], skeletal muscle [10,11], vascular smooth muscle [12], etc. Also, published work suggests that TRPV1 in the brain.…”
Section: Trpv1: Capsaicin Receptormentioning
confidence: 99%